Pravni vidik ureditve delovnega časa visokošolskih učiteljev in pravica do odklopa - Tancer Verboten, Mojca (Annales. Series historia et sociologia, 2024)
The special position of higher education teachers is determined by the nature of their work. They are employed by the university through an employment contract, and it is therefore indispensable for their protection under the labour law that the legislation is drafted in a way that acknowledges both the specificities arising from the role of the university and from the characteristics of their work. When performing their tasks, scientific research work is expected in addition to their teaching obligation, raising the question of the employer‘s possibility to define such work in advance. At the same time, it is required for the academic profession to conform to the working time regulation, taking into account the minimum standards of labour law. The working time of higher education teachers consists of various forms of work obligations which are unevenly distributed, especially during the teaching period when a higher education teacher has an individually precisely-determined teaching load. Due to the uneven distribution of working time, it is thus necessary to determine a reference period for the time when the workload of higher education teachers must be offset. Since the length of working time during which higher education teachers perform other forms of work obligations is provided only in flat-rate values by internal acts of individual universities, the nature of their work should be regulated in the form of flexible working hours. It is therefore a question of whether and to what extent higher education teachers can schedule their own working hours, which at the same time affects the regulation of the new right established also for the higher education teachers, i.e. the right to disconnect. Related to the specific nature of the work of higher education teachers, the question arises as to how to regulate the right to disconnect in the university environment, and what measures to adopt. It is the author’s belief that consideration should be given on how to educate and guide higher education teachers on the time and manner of their availability to the employer. The use of the right to disconnect brings quite a few open questions, which for the time being are left to the autonomous regulation of the universities, however, it would be more appropriate for them to be addressed by the relevant collective agreement
Keywords: anatomija univerze; delovni čas; pogodba o delu; pravica do odklopa; visokošolski učitelji